2022
DOI: 10.3389/fbinf.2022.959160
|View full text |Cite
|
Sign up to set email alerts
|

Improving peptide-protein docking with AlphaFold-Multimer using forced sampling

Abstract: Protein interactions are key in vital biological processes. In many cases, particularly in regulation, this interaction is between a protein and a shorter peptide fragment. Such peptides are often part of larger disordered regions in other proteins. The flexible nature of peptides enables the rapid yet specific regulation of important functions in cells, such as their life cycle. Consequently, knowledge of the molecular details of peptide-protein interactions is crucial for understanding and altering their fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 47 publications
5
104
0
Order By: Relevance
“…They concluded that this assay had a better prediction score for identifying stronger peptide binders that also adopt stable secondary structures upon binding [ 92 ]. Johansson-Åkhe et al [ 93 ] also show the importance of AlphaFold, in this case, AlphaFold-Multimer. AlphaFold-Multimer is shown to be capable of predicting the structure of peptide–protein complexes with acceptable or better accuracy than previous models and also has the capacity to predict whether a peptide and a protein will interact, thus improving peptide–protein docking [ 93 ].…”
Section: Computational Methods For Predicting Checkpoint Inhibitorsmentioning
confidence: 95%
See 1 more Smart Citation
“…They concluded that this assay had a better prediction score for identifying stronger peptide binders that also adopt stable secondary structures upon binding [ 92 ]. Johansson-Åkhe et al [ 93 ] also show the importance of AlphaFold, in this case, AlphaFold-Multimer. AlphaFold-Multimer is shown to be capable of predicting the structure of peptide–protein complexes with acceptable or better accuracy than previous models and also has the capacity to predict whether a peptide and a protein will interact, thus improving peptide–protein docking [ 93 ].…”
Section: Computational Methods For Predicting Checkpoint Inhibitorsmentioning
confidence: 95%
“…One of the most recently developed computational methods, AlphaFold, has revolutionized structural biology by predicting highly accurate structures of proteins and their complexes with peptides, antibodies and proteins [ 92 , 93 , 94 ]. In addition to that, AlphaFold can also be useful for protein–peptide systems and drug discovery, as it can help identify the highest affinity binder among a set of peptides.…”
Section: Computational Methods For Predicting Checkpoint Inhibitorsmentioning
confidence: 99%
“…Models of complexes between conspecific GRASP/Golgin-45 pairs were built with the Colab implementation of AlphaFold2 77 , using MMseqs2 to generate multiple sequences alignments 90 . To obtain reliable predictions of the protein-peptide complexes, AlphaFold-Multimer version v2 was used, with 12 recycles for the generation of each model 91 . Complexes were built without the use of structural templates and without Amber refinement as this step does not introduce substantial improvement, while significantly increasing computational time.…”
Section: Star Methodsmentioning
confidence: 99%
“…90 . To obtain reliable predictions of the protein-peptide complexes, AlphaFold-Multimer version v2 was used, with 12 recycles for the generation of each model 91 . Complexes were built without the use of structural templates and without Amber refinement as this step does not introduce substantial improvement, while significantly increasing computational time.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation